Air bacteriological quality in Taha Al-Quran Education Park, Bima District - Sri Wahyuningsih; Wahyudin Wahyudin; Mulhidin Mulhidin (Jurnal Pijar Mipa, 2023)
Qur'an Education Park is a nonformal education facility that has many students. Apart from being a place for learning knowledge, Quran Education Park also has the potential to become a place of a transmission. One of the factors influencing the spread of disease is the presence of germs in the Air. This study aims to determine the air quality in the classroom. The study showed the number of bacteria in the classroom at the Taha Qur'an Education Park, Sanggar District, Bima Regency. This type of research is analytic observational with a cross-sectional study approach. The highest number of bacterial colonies was in room 2, with the measurement time in the afternoon with a total of 2569 CFU/m3. Characterization showed that the average bacteria were gram-positive, and characteristics according to the average colony were pinpoint size. Conclusions from the research on quality air bacteriology in the Taha Quran Education Park do not meet the requirements according to KEPMENKES RI No. 1204/MENKES/SK/X/2002 concerning classroom (200-500 CFU/m3).